The Perceptions of Children at a Children Day Care Centre about the Authority of a Social Worker - Grudulaitė, Lina (Acta Paedagogica Vilnensia, 2016)
The article presents the theoretical explanations of the concept of authority and its ethical implications for social work practice. It discusses the empirical findings of the qualitative case study conducted at the day care centre X. The perceptions of children, what authority of a social worker means and consists of and how to gain it, are presented. The article includes a detailed description of the specific context of the case study and indicates the selected research methods. The degree of reliability and validity of research study are also discussed. The empirical data of the case study is analysed and discussed and conclusions are presented.